Displacement and migration in the international climate negotiations: Loss and damage debate offers new scope for action - Nadine Biehler; Nadine Knapp; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2023)
Climate change is leading to increasing displacement and migration, as well as involuntary immobility. The associated challenges and costs have long been neglected in the international climate negotiations. Until now, efforts to open up mobility choices for people negatively affected by climate change have been chronically underfunded. One important starting point for changing this is the explicit reference to human mobility in the new Loss and Damage Fund. However, financial resources and technical support alone are not enough. In order to meet the epochal challenge of climate change-induced human mobility ambitious migration policy solutions are needed, including planned relocation and the consideration of climate change impacts in the management of labour migration.
Keywords: 320; displacement; migration; climate change; International Climate Negotiations; COP 28; loss und damage; Internal Displacement Monitoring Centre (IDMC); Intergovernmental Panel on Climate Change (IPCC)